2017
DOI: 10.1093/gerona/glx098
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Frailty Among Community-Dwelling Chinese Older Adults: The China Health and Retirement Longitudinal Study

Abstract: We demonstrated the utility of the PFP scale in identifying frail Chinese elders, and found substantial sociodemographic and regional disparities in frailty prevalence. The PFP scale may be incorporated into clinical practice in China to identify the most vulnerable elders to reduce morbidity, prevent disability, and enable more efficient use of health care resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
183
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(219 citation statements)
references
References 24 publications
(26 reference statements)
29
183
4
3
Order By: Relevance
“…The findings of this study show that the prevalence of frailty in older adults in China is 9.9%, based on the CGA‐FI criteria; southwestern China had the highest rate (12.7%) and northeastern China the lowest (2.3%), consistent with previous studies . A recent study reported an overall prevalence of frailty of 7.0%, ranging from 3.3% in the southeast and northeast to 9.1% in the northwest, when determined using the Fried criteria .…”
Section: Discussionsupporting
confidence: 88%
“…The findings of this study show that the prevalence of frailty in older adults in China is 9.9%, based on the CGA‐FI criteria; southwestern China had the highest rate (12.7%) and northeastern China the lowest (2.3%), consistent with previous studies . A recent study reported an overall prevalence of frailty of 7.0%, ranging from 3.3% in the southeast and northeast to 9.1% in the northwest, when determined using the Fried criteria .…”
Section: Discussionsupporting
confidence: 88%
“…[2][3][4] As population aging has become a prominent policy and public health issue, research on aging has proliferated in China over the past decade, with a focus on the mechanisms, epidemiology, and interventions for noncommunicable diseases, disability, and frailty. [5][6][7][8][9][10][11][12] In contrast, little is known about Chinese older adults who are on the other end of the continuum-persons who maintain a high level of health and function in late life. Identifying older adults with exceptional health and characterizing their sociodemographic, lifestyle, and physiological profiles may help uncover healthy aging-and longevity-associated factors, which may be useful for clinical, epidemiological, and policy applications.…”
mentioning
confidence: 99%
“…Os resultados desta pesquisa mostram uma maior prevalência de fragilidade (17,7%) quando comparado a outros estudos brasileiros, os quais apresentam 8,7% 16 e 9,1% 11 da população idosa como frágil e estudos internacionais que encontraram prevalência de 6,9% 10 e 7,0% 17 . Também está aumentada quando comparada a prevalência de 10,7% encontrada em uma revisão sistemática com mais de 60.000 idosos residentes na comunidade 18 .…”
Section: Discussionunclassified